Answer:
The statement is true for every n between 0 and 77 and it is false for ![n\geq 78](https://tex.z-dn.net/?f=n%5Cgeq%2078)
Step-by-step explanation:
First, observe that, for n=0 and n=1 the statement is true:
For n=0: ![\sum^{n}_{i=0} (2i)^4=0 \leq 0=(4n)^4](https://tex.z-dn.net/?f=%5Csum%5E%7Bn%7D_%7Bi%3D0%7D%20%282i%29%5E4%3D0%20%5Cleq%200%3D%284n%29%5E4)
For n=1: ![\sum^{n}_{i=0} (2i)^4=16 \leq 256=(4n)^4](https://tex.z-dn.net/?f=%5Csum%5E%7Bn%7D_%7Bi%3D0%7D%20%282i%29%5E4%3D16%20%5Cleq%20256%3D%284n%29%5E4)
From this point we will assume that ![n\geq 2](https://tex.z-dn.net/?f=n%5Cgeq%202)
As we can see,
and
. Then,
![\sum^{n}_{i=0} (2i)^4 \leq(4n)^4 \iff \sum^{n}_{i=0} i^4 \leq 16n^4](https://tex.z-dn.net/?f=%5Csum%5E%7Bn%7D_%7Bi%3D0%7D%20%282i%29%5E4%20%5Cleq%284n%29%5E4%20%5Ciff%20%5Csum%5E%7Bn%7D_%7Bi%3D0%7D%20i%5E4%20%5Cleq%2016n%5E4)
Now, we will use the formula for the sum of the first 4th powers:
![\sum^{n}_{i=0} i^4=\frac{n^5}{5} +\frac{n^4}{2} +\frac{n^3}{3}-\frac{n}{30}=\frac{6n^5+15n^4+10n^3-n}{30}](https://tex.z-dn.net/?f=%5Csum%5E%7Bn%7D_%7Bi%3D0%7D%20i%5E4%3D%5Cfrac%7Bn%5E5%7D%7B5%7D%20%2B%5Cfrac%7Bn%5E4%7D%7B2%7D%20%2B%5Cfrac%7Bn%5E3%7D%7B3%7D-%5Cfrac%7Bn%7D%7B30%7D%3D%5Cfrac%7B6n%5E5%2B15n%5E4%2B10n%5E3-n%7D%7B30%7D)
Therefore:
![\sum^{n}_{i=0} i^4 \leq 16n^4 \iff \frac{6n^5+15n^4+10n^3-n}{30} \leq 16n^4 \\\\ \iff 6n^5+10n^3-n \leq 465n^4 \iff 465n^4-6n^5-10n^3+n\geq 0](https://tex.z-dn.net/?f=%5Csum%5E%7Bn%7D_%7Bi%3D0%7D%20i%5E4%20%5Cleq%2016n%5E4%20%5Ciff%20%5Cfrac%7B6n%5E5%2B15n%5E4%2B10n%5E3-n%7D%7B30%7D%20%5Cleq%2016n%5E4%20%5C%5C%5C%5C%20%5Ciff%206n%5E5%2B10n%5E3-n%20%5Cleq%20465n%5E4%20%5Ciff%20465n%5E4-6n%5E5-10n%5E3%2Bn%5Cgeq%200)
and, because
,
![465n^4-6n^5-10n^3+n\geq 0 \iff n(465n^3-6n^4-10n^2+1)\geq 0 \\\iff 465n^3-6n^4-10n^2+1\geq 0 \iff 465n^3-6n^4-10n^2\geq -1\\\iff n^2(465n-6n^2-10)\geq -1](https://tex.z-dn.net/?f=465n%5E4-6n%5E5-10n%5E3%2Bn%5Cgeq%200%20%5Ciff%20n%28465n%5E3-6n%5E4-10n%5E2%2B1%29%5Cgeq%200%20%5C%5C%5Ciff%20465n%5E3-6n%5E4-10n%5E2%2B1%5Cgeq%200%20%5Ciff%20465n%5E3-6n%5E4-10n%5E2%5Cgeq%20-1%5C%5C%5Ciff%20n%5E2%28465n-6n%5E2-10%29%5Cgeq%20-1)
Observe that, because
and is an integer,
![n^2(465n-6n^2-10)\geq -1 \iff 465n-6n^2-10 \geq 0 \iff n(465-6n) \geq 10\\\iff 465-6n \geq 0 \iff n \leq \frac{465}{6}=\frac{155}{2}=77.5](https://tex.z-dn.net/?f=n%5E2%28465n-6n%5E2-10%29%5Cgeq%20-1%20%5Ciff%20465n-6n%5E2-10%20%5Cgeq%200%20%5Ciff%20n%28465-6n%29%20%5Cgeq%2010%5C%5C%5Ciff%20465-6n%20%5Cgeq%200%20%5Ciff%20n%20%5Cleq%20%5Cfrac%7B465%7D%7B6%7D%3D%5Cfrac%7B155%7D%7B2%7D%3D77.5)
In concusion, the statement is true if and only if n is a non negative integer such that ![n\leq 77](https://tex.z-dn.net/?f=n%5Cleq%2077)
So, 78 is the smallest value of n that does not satisfy the inequality.
Note: If you compute
for 77 and 78 you will obtain: